Penerapan Sanksi Pidana Terhadap Kasus Kelalaian Pengemudi Yang Menyebabkan Kecelakaan Di Jalan Raya Berdasarkan Undang-Undang Nomor 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan Wilayah Hukum Kepolisian Sektor Kelayang - Nova Rifadilla; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In Indonesia, current traffic is still quite alarming. The negligence of road users in traffic holes weoften encounter everyday often causes high height. Human factors consist of other factors, namely roadfactors, vehicle factors, natural factors. The purpose of this study was to determine whether in the case oftraffic and traffic disasters in accordance with Law Number 22 Year 2009 concerning Traffic andTransportation and the factors that encourage law enforcement in cases of negligence.This type of research is sociological legal research while viewed from its nature this research isdescriptive. This research uses primary data, namely data obtained directly from the first. And secondarydata, namely data that has been prepared.The results of this study are the application of provisions in cases of traffic and traffic accidentsbased on Law Number 22 of 2009 concerning Road Traffic and Transportation. For perpetrators who causedeath victims are subject to Article 310 paragraph (4) and Article 311 paragraph (1) of Law Number 22Year 2009 and Article 359 of the Criminal Code. In Article 310 paragraph (4) shall be punished withparents for a maximum of 12 (twelve) years or a maximum fine of Rp. 24,000,000.00 (twenty four millionrupiahs). In Article 311 paragraph (1) the offender is punished with a maximum of 1 (one) year of criminalor a maximum fine of Rp. 3,000,000 (three million rupiah). Article 359 The Criminal Code conducts threatswith other people for at most one year. However, users who commit negligence resulting in death victimscannot be used as which is actually in the applicable rules. Motorists are indeed subject to errors in theform of administrative fees, but are different, which in the first case is Rp. 5,000,000 (five million rupiah)whereas in the second case, the driver is subject to administrative sanctions of Rp. 200,000 (two hundredthousand). Factors that strengthen law enforcement in cases of negligence of tools in the freedom of crossthat shape death are their own legal factors, law enforcement factors, factors of facilities and facilities thatsupport law enforcement, factors of criminal and non-criminal policy factors.Keywords: criminal sanctions, negligence, highway accidents.